Knowledge of language its nature, origin, and use - Chomsky, Noam (New York Praeger, 1986)
"Attempts to indentify the fundamental concepts of language, argues that the study of language reveals hidden facts about the mind, and looks at the impact of propaganda."
Knowledge of language as a focus of inquiry -- Concepts of language -- Facing Plato's problem -- Questions about rules -- Notes on Orwell's problem
Includes index.
Bibliography: pages 288-296.
CSSP-9049 donated by Dr. Videa De Guzman.
Keywords: Language and languages